The effects of qishen granules for patients with chronic heart failure: A multicenter randomized double-blind placebo-controlled trial - Du, Kangjia; Liu, Junjie; Tan, Nannan; Huang, Xinyi; Wang, Juan; Zhao, Huihui; Wang, Wei (Frontiers in Pharmacology, 2022)
Abstract Background: Despite advancements in chronic heart failure (CHF) treatment, the effect often remains unsatisfactory and unstable. More effective therapies are needed. Qishen granules (QSG) are a novel Chinese botanical drug effective in treating CHF in animal models, but clinical evidence remains inadequate. Objective: This study aims to evaluate the effects of QSG on patients with CHF. Methods: We enrolled CHF patients in this 12-week, randomized, double-blind, placebo-controlled trial, and randomly assigned them to the QSG (twice a day, 6.8g granules at once) or placebo group. The primary endpoint was a change in the plasma N-terminal pro-B-type natriuretic peptide (NT-proBNP) level after treatment. The secondary outcome consists of the New York Heart Association (NYHA) functional classification, 6-minute walking distance (6MWD), TCM syndrome integral scale, quality of life, and echocardiographic index. Results: A total of 191 patients completed the 12-week follow-up period, with 94 in the QSG group and 97 in the placebo group. The Qishen granules group demonstrated a considerably greater reduction in NT-proBNP than the placebo group (50% vs. 32% for QSG vs. placebo, respectively; p=0.011). Patients who received QSG performed better in the NYHA functional rank, 6MWD, TCM syndrome integral scale, and quality of life (p<0.05). The QSG group performed better in HFrEF patients regarding the efficiency of NT-proBNP. There was no statistical significance in the change in evaluated safety parameters, such as blood routine and biochemistry. Conclusions: Based on standard treatment, Qishen granules further reduced the levels of NT-proBNP when compared with placebo. Together with other outcomes, our findings suggest that QSG could be used in combination therapy for CHF. Trial registration: URL: www.clinicaltrials.gov; Unique identifier: NCT03027375. Registered October 9, 2017